A Study on the Relevance of Vocational Education with Special Reference to the Indian Society - Chandan Patgiri (International Journal of Advanced Science and Technology, 2020)
In the Indian society we can see that many people getting lot of numbers of degree but they are unable to getting a suitable job for their future life. Many young people committed crime due to lack of jobs and unemployment problems and many feel frustrated due to not geeting a appropriate job on their life. The unemployment problem so increases day by day in Indian society. This problem is also take place in the North Eastern India. Specially if we see that there is one post of a government jobs in a particular field and the number of candidate much higher than expectation. People only looking for government job for their secure life. They want the government job by hook and crook. But vocational education is a process which can solve the problem of unemployment. Many of the businesses are the most richest persons of the world which are directly or in directly related to vocational training or education. So there is an need to study about the relevance of the vocational education by seeing the present situation of the nation .Vocational education refers to the those skills which helps them to expertise in a particular field and helps to self confident and self reliant in the society by earning his/her own bread and butter by his own efforts .